Misku's story - International Livestock Research Institute (International Livestock Research Institute, 2012)
This is the story of Misku Abafaris, a woman farmer in Ethiopia, who was interviewed in 2010 about the changes in her life as a result of interventions by the International Livestock Research Institute (ILRI)-led Improving Productivity and Market Success of Ethiopian Farmers (IPMS) project. Since 2006, ILRI has been working closely with Ethiopia's Ministry for Agriculture and Rural Development to improve farmers' livelihoods.